1999
DOI: 10.1097/00004714-199912000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Glycine (Bioglycin) on Memory and Attention in Young and Middle-Aged Adults

Abstract: The N-methyl D-aspartate receptor complex is involved in the mechanism of long-term potentiation, which is thought to be the biological basis of learning and memory. This complex can be manipulated in a number of ways, one of which is through the strychnine-insensitive glycine receptor coagonist site. The effects of Bioglycin(Konapharma, Pratteln, Switzerland), a biologically active form of the amino acid glycine, were therefore studied in healthy students (mean age, 20.7 years) and middle-aged men (mean age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 35 publications
1
27
0
2
Order By: Relevance
“…Previous work has demonstrated that the consumption of high doses of glycine can improve memory in volunteers [40] and decrease mortality in stroke [41]. The neurochemical basis for this phenomenon is still unclear, but presynaptic effects of glycine which we described can contribute to its pharmacological action.…”
Section: Discussionmentioning
confidence: 51%
“…Previous work has demonstrated that the consumption of high doses of glycine can improve memory in volunteers [40] and decrease mortality in stroke [41]. The neurochemical basis for this phenomenon is still unclear, but presynaptic effects of glycine which we described can contribute to its pharmacological action.…”
Section: Discussionmentioning
confidence: 51%
“…Significant cognitive effects were neither observed following acute oral administration of 0.8 g/kg GLY (Palmer et al, 2008) or 50 mg D-cycloserine DCS (D'Souza et al, 2000) which acts as a partial NMDAR agonist. In contrast, 100 mg GLY sublingually (File et al, 1999) and oral administration of 1.2 g of the GLY precursor milacemide (Schwartz et al, 1991) were reported to improve performance of memory tasks in healthy subjects. Moreover, Onur et al (2010) and Kuriyama et al (2011) have recently shown that DCS (250 mg and 100 mg single doses) improve declarative and procedural learning, respectively.…”
Section: Introductionmentioning
confidence: 86%
“…However, to reduce the complexity of the current study, one single dose was utilised. The time of electrophysiological recording was chosen to coincide with the maximum glycine plasma concentration, which has been reported to peak at approximately 30-45 min (Truong and Fahn 1988;Gannon et al 2002) and cognitive and electrophysiological effects reported within this time window (File et al 1999). …”
Section: Glycine Dosage and Administration Timementioning
confidence: 99%
“…One study has investigated the effects of intravenous glycine (0.1 or 0.2 g/kg) on healthy controls and failed to find an effect on behavioral measures, cognitive functioning, or acoustic startle response (D'Souza et al 2000). Several studies using drugs that stimulate glycine neurotransmission, for instance 0.1 g of Bioglycin (a biologically active form of glycine; File et al 1999) and 0.4 and 1.2 g of milacemide (a glycine precursor; Saletu and Grunberger 1984;Schwartz et al 1991), have demonstrated improvements in memory and vigilance tasks, while a subsequent study found no effects with 0.4 g of milacemide (Camp-Bruno and Herting 1994). Thus, we are not in a position to comment on the cognitive effects of high doses, as previously employed for AGT in patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%